The Role of Human Resources in Building a Marketing Team Responsive to Global Market Changes: A Systematic Literature Review - Supriadi, Yudi Nur; Rialmi, Zackharia; Iswanto, Dedy; Saleh, Amin; Ramadhan, Miftahus Surur (LifeSciFi, 2025)
This research uses the PRISMA 2020-based Systematic Literature Review (SLR) approach to analyze the role of Human Resources (HR) in building a marketing team that is responsive to global market changes. This research aims to explore how HR management can improve the ability of marketing teams to adapt quickly to market changes, as well as to identify the skills and competencies required by marketing team members. A literature search was conducted through databases such as Scopus, Web of Science, and ScienceDirect. The results show that HR strategies that integrate technologies such as Data-Driven Decision-Making and blockchain, as well as the development of adaptation skills and responsive leadership, are highly effective in enhancing the marketing team's ability to respond to global market dynamics. In addition, continuous training and the development of a flexible organizational culture play an important role in creating innovative and responsive marketing teams. Challenges such as inequality in technology adoption, international regulatory differences, and limitations of the research methodology still pose barriers to the practical application of these findings. This study suggests that future research should delve deeper into the influence of innovative technologies in HRM and strategies that can overcome real-world implementation challenges.